PROMOTING STUDENTS’ INDEPENDENT LEARNING STRATEGIES IN FACING ONLINE LEARNING: STUDENTS’ VOICES - Ratih Inayah; Sri Supiah Cahyati (English Journal Literacy Utama, 2023)
This study, utilizing a narrative inquiry approach, explores the perceptions of eighth semester English education students regarding online learning activities facilitated by their instructors over a period of twenty months during the Covid-19 pandemic. The participants included 30 students who were engaged in online learning during the pandemic. The study employed three audio-recorded post-teaching conferences and three guided group interviews to gather data on the participants' online learning experiences during the pandemic. The qualitative data was analyzed using content analysis techniques. The results indicated that, in addition to the challenges that arise in online learning, such as mastery of learning materials and the volume of assignments given by instructors, students also expected more detailed feedback from their instructors across various teaching contexts, for several reasons. The findings suggest that differences in perceptions regarding online learning and the need for students to develop more independent learning strategies and recommendations are important topics for further discussion.